The answer to the question is a
Answer: D
Step-by-step explanation:
A. 3 + -7 < -4
-4 < -4
X
this one isn’t a solution
B. 3 + -7 ≤ -4
-4 ≤ -4
this works, let’s try the other equation
3(3) + 2(-7) < -5
9 + -14 < -5
-5 < -5
X
this one doesn’t work either, let’s go on to the next one
C. the first equation is the same as the first one in A, and that didn’t work, so we know that the whole thing doesn’t work and we don’t have to do any math
D. we know the first equation works because we did it in B
let’s go on to the second equation
3(3) + 2(-7) ≤ -5
9 -14 ≤ -5
-5 ≤ -5
this works, so that means that both equations work and the whole thing works :)
Answer:
B
Step-by-step explanation:
For this equation, we can just plug in the equation of m in for m. This makes the equation: n - 2 + 3n = 10. We then only have to solve for n. We add 2 to both sides, making it n + 3n = 12, is which is also 4n = 12. We then divide both sides by 4, getting n = 3. The only answer saying n = 3 is the first.